2010
DOI: 10.1088/0953-4075/43/21/215401
|View full text |Cite
|
Sign up to set email alerts
|

Group velocity coupling and synchronization-like phenomenon of two light beams based on coherent population oscillations

Abstract: Abstract. We report on the control of the slow and fast light propagation velocity of two light beams (at 1550 nm and 980 nm) through an erbium doped fiber amplifier by means of coherent population oscillations. We modulate the amplitude of both beams with the same frequency so that the relative phase between both modulations allows us to control their group velocities. The same group velocity, in absolute value, is achieved when beams are modulated in phase or phase opposition. The experimental results are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Schweinsberg et al measured slow light and fast light propagation in a fiber in 2006 [8]. Melle et al studied both 1550 nm and 980 nm lasers into an erbium-doped fiber amplifier to observe slow light and superluminal propagation in 2010 [9]. In 2011, Melle et al reported pulse width dependent subluminal and superluminal propagation in highly doped erbium fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Schweinsberg et al measured slow light and fast light propagation in a fiber in 2006 [8]. Melle et al studied both 1550 nm and 980 nm lasers into an erbium-doped fiber amplifier to observe slow light and superluminal propagation in 2010 [9]. In 2011, Melle et al reported pulse width dependent subluminal and superluminal propagation in highly doped erbium fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Lauro et al observed the slow light phenomenon in a Tm 3+ -doped yttrium-aluminum-garnet crystal [10]. In 2010, Melle et al studied 1550 nm and 980 nm lasers in an erbium-doped fiber (EDF) amplifier to observe slow light and superluminal propagation [11]. In 2013, slow and fast light via two-wave mixing in an ytterbium-doped fiber at 1064 nm were investigated in detail [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Lauro et al observed a slow light phenomenon in a Tm 3+ -doped yttrium-aluminum-garnet crystal [6]. In 2010, Melle et al studied both 1550 nm and 980 nm lasers in an erbium-doped fiber (EDF) amplifier to observe slow light and superluminal propagation [7]. In 2013, Enrique et al investigated in detail slow and fast light via two-wave mixing in an ytterbium-doped fiber at 1064 nm [8].…”
Section: Introductionmentioning
confidence: 99%